PERBANDINGAN MASLAHAT DALAM PANDANGAN IMAM MALIK DENGAN IMAM AL-GAZALI - Masse, Rahman Ambo (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2012)
The idea of benefit to Imam Malik has a style of its own, which makes the beneficiaries as a method of law that can provide special insight into the passage of a general nature, and even tend to practice the beneficiaries rather than nas, nas contextually if it is not in accordance with the socio society. Beneficiaries in view of al-Ghazali is an expression of something that will benefit and refused harm, the beneficiaries can maintain the intent Syaria. The purpose of the Syariah concerning humans, there are five cases, which is preserve religion, life, intellect, lineage, and wealth. What are five things related to it are called beneficiaries. Otherwise everything can destroy five of the above named mafsadat. Differences thought benefit to Imam Malik and Imam al-Ghazali lies in the use of the ratio in the determination of the existence of a benefit. Imam Malik freer in the use of ratios to determine the existence of a benefit. While Imam al-Ghazali still assume that the ratio is able to capture the presence or absence of a benefit as justified by the revelation. Thus the applicative, Imam Malik freer in determining beneficiaries than Imam al-Ghazali